Development Of Learning Media For Animal Life Cycle Puzzles In Science Subjects At Fourth Grade Elementary School - Tiyas, Nanda Setyaning; Nulhakim, Lukman; Syachruroji, Ahmad (Universitas Pendidikan Ganesha, 2020)
The low activity and participation of students in learning due to the teacher's lack of learning models during the learning process. This research aims to develop learning media of animal life cycle puzzle and determine the feasibility and students’ response to the product being developed in fourth-grade elementary school. The purpose of developing animal life cycle puzzle was obtained from the results during pre-research that the teacher explained the animal life cycle material with the lecture and teacher center method, besides that the teacher also only focused on student books as a learning medium so that students looked passive in the learning process. The research method used a research and development method that has been modified by Sugiyono, which begins with the problem analysis, data collection, product design, design validation, product design revision, and product trial trials. Based on the results of the feasibility test of the learning media of animal life cycle puzzle get an average score of eligibility by a design expert team of 86, 35% with the criteria of interpretation category